Republic of Poland : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2003 Article IV Consultation highlights that the economy of the Republic of Poland began to recover during 2002 from the sharp weakening of growth in 2000-01, but the recovery is fragile. Private consumption picked up gradually, fueled by rising real fiscal transfers, easing monetary policy, and a drop in the savings ratio. Exports outpaced rather weak market growth as competitiveness improved. The recovery also reflected a lessening of negative influences: a sharp drop in inventories ended, and the contraction of fixed investment lessened.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet